Pengaruh Marketing Mix terhadap Minat Beli Konsumen Muslim pada Shopee : Studi Kasus Mahasiswa Darussalam Gontor Kampus Robithoh - Dio Samudra (Institut Agama Islam Negeri Parepare, 2022)
This research takes the basis of the phenomenon of increasing the use of online shopping platforms, especially Shopee. The purpose of the study was to examine the impact of the Marketing Mix on student purchase intention at the Robithoh Darussalam Gontor Campus through the Shopee platform. This research methodology uses a quantitative approach with a subjective type, using primary data collected through questionnaires. The analysis method used is multiple regression analysis. The research sample involved 84 respondents who were selected using the Slovin formula technique and random sampling technique. The results showed that (1) the product variable has a positive and significant influence on student purchase intention, (2) the price variable has a positive and significant influence on student purchase intention. (3) Promotion variables also have a positive and significant influence on student purchase intention. All of these variables are part of the influence of the Marketing Mix on student purchase intention at the Robithoh Darussalam Gontor Campus.